Structuring Corporate Sukuk Through The Lens of Maqasid Al-Shariah: A Qualitative Insight From Sharia Advisory Council (SAC) Of Islamic Financial Institutions ((IFIs) - Fauzias Mat Nor; Nur Ainna Ramli; Syahidawati Hj. Shahwan; Nurul Aini Muhamed; Norhaziah Nawai; Ainulashikin Marzuki; Nur Atika Atan (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA